A review of fog computing and its simulators. (3rd April 2022) - Kaler, Sonam; Sharma, Amit; Yatoo, Arshad Ahmad
Abstract: Fog computing is defined as the distribution of computing resources between the data devices and the cloud or any other data centre in a distributed computing infrastructure or process. This paper briefly reviews the various definitions, applications, architecture and fog simulators proposed by researchers over the years. In this paper, a comparison table is presented which highlights the key features of simulators available like FogtorchII, iFogSim, Fogbus, MyiFogSim etc.